La Rivista del Nuovo Cimento - Cifarelli, Luisa; Bracco, Angela; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
La Rivista del Nuovo Cimento is a monthly journal of long review articles. It deals with topics of particular scientific interest and with up-to-date issues pertaining to different fields of physics. These reviews, which illustrate the state of the art of specific topics of relevant importance in modern physics, usually are invited papers, which are peer-reviewed before publication.
Keywords: Physics; Physics, general